Cell lineage analysis of maize bundle sheath and mesophyll cells. - Langdale, J; Lane, B; Freeling, M; Nelson, T (1989)
Maize leaves are divided into repeated longitudinal units consisting of vascular tissue, bundle sheath (BS), and mesophyll (M) cells. We have carried out a cell lineage analysis of these cell types using six spontaneous striping mutants of maize. We show that certain cell division patterns are preferentially utilized, but not required, to form the characteristic arrangement of cell types. Our data suggest that early in development a central cell layer is formed, most frequently by periclinal divisions in the adaxial subepidermal layer of the leaf primordium. Lateral and intermediate veins are initiated in this central layer, most often by divisions which contribute daughter cells to both the procambium and the ground meristem. These divisions generate "half vein" units which comprise half of the bundle sheath cells around a vein and a single adjacent M cell. We show that intermediate veins are multiclonal both in this transverse direction and along their lengths. BS cells are more closely related to M cells in the middle layer of the leaf than to those in the upper and lower subepidermal layers. An examination of sector boundaries has shown that photosynthetic differentiation in M cells is affected by the phenotype of neighboring BS cells.